Enhancement of ionic conductivity in polyacrylamide based polymer electrolytes for tin-air batteries - Sumathi Subramaniam (N/A, 2017)
Enhancement of ionic conductivity in polyacrylamide based polymer electrolytes for tin-air batteries by Sumathi Subramaniam